Agricultura orgânica no Brasil: caracterização a partir do censo agropecuário - 2017 - ISABEL BENITES PAREDES CHAVES (2024)
Concerns about food security, reducing environmental impacts and sustainability highlight organic agriculture as an alternative to conventional agriculture. Furthermore, organic agriculture has social, economic and environmental bases that aim to improve environmental preservation and reduce dependence on pesticides, providing better health for people and conserving natural resources. In this sense, this research sought to analyze the characteristics of organic agriculture in Brazil, according to the analysis of data from the 2017 Agricultural Census. The quantitative research consisted of a systematic review and descriptive statistics on organic agriculture, based on data collected in SIDRA tables in the last 2017 Agricultural Census from the Brazilian Institute of Geography and Statistics (IBGE). The results show that 64,690 organic establishments in Brazil correspond to 1.28% of the national total, predominantly with a total area between 20 and 50 hectares, the producers are owners of the land, belonging to family farming, they receive technical guidance from the Government, they are not associated with no class and exclusively practice vegetable production. The majority of organic producers are men, aged between 55 and 65 years old, white color/race and fall into family farming - Pronaf B. In addition to the characteristics of organic establishments and producers, it was also observed that 63.69% of the 5,073 826 agricultural establishments did not use pesticides in Brazil in 2017. In view of the above, it is concluded that public policies are important to maintain and increase organic production, as well as investments in projects that promote the practice of organic cultivation in Brazil. Since the development of organic agriculture in large Brazilian regions is linked to the contribution of public policies, as the results show that 76.26% belong to family farming and 75.76% do not receive adequate technical guidance. Furthermore, Brazil exploits only 0.63% of the total arable area with organic production, having great growth potential due to its extensive agricultural area.